Cholinergic Receptor Blockade in the VTA Attenuates Cue-Induced Cocaine-Seeking and Reverses the Anxiogenic Effects of Forced Abstinence. (10th August 2019) - Nunes, Eric J.; Bitner, Lillian; Hughley, Shannon M.; Small, Keri M.; Walton, Sofia N.; Rupprecht, Laura E.; Addy, Nii A.
Abstract: Drug relapse after periods of abstinence is a common feature of substance abuse. Moreover, anxiety and other mood disorders are often co-morbid with substance abuse. Cholinergic receptors in the ventral tegmental area (VTA) are known to mediate drug-seeking and anxiety-related behavior in rodent models. However, it is unclear if overlapping VTA cholinergic mechanisms mediate drug relapse and anxiety-related behaviors associated with drug abstinence. We examined the effects of VTA cholinergic receptor blockade on cue-induced cocaine seeking and anxiety during cocaine abstinence. Male Sprague–Dawley rats were trained to self-administer intravenous cocaine (~ 0.5 mg/kg/infusion, FR1 schedule) for 10 days, followed by 14 days of forced abstinence. VTA infusion of the non-selective nicotinic acetylcholine receptor antagonist mecamylamine (0, 10, and 30 μg/side) or the non-selective muscarinic receptor antagonist scopolamine (0, 2.4 and 24 μg /side) significantly decreased cue-induced cocaine seeking. In cocaine naïve rats, VTA mecamylamine or scopolamine also led to dose-dependent increases in open arm time in the elevated plus maze (EPM). In contrast, rats that received I.V. cocaine, compared to received I.V. saline rats, displayed an anxiogenic response on day 14 of abstinence as reflected by decreased open arm time in the EPM. Furthermore, low doses of VTA mecamylamine (10 μg /side) or scopolamine (2.4 μg /side), that did not alter EPM behavior in cocaine naive rats, were sufficient to reverse the anxiogenic effects of cocaine abstinence. Together, these data point to an overlapping role of VTA cholinergic mechanisms to regulate relapse and mood disorder-related responses during cocaine abstinence. Highlights: VTA mAChR and nAChR blockade attenuates cue-induced cocaine seeking on forced abstinence day 14. VTA mAChR and nAChR blockade produces an anxiolytic-like effect on the elevated plus maze in cocaine naive rats. I.V. cocaine self-administration and forced abstinence produces an anxiogenic-like effect on the elevated plus maze. VTA mAChR and nAChR blockade attenuates the cocaine-induced anxiogenic-like effect on the elevated plus maze.